2023
DOI: 10.3389/fnins.2023.1125281
|View full text |Cite
|
Sign up to set email alerts
|

Six mitophagy-related hub genes as peripheral blood biomarkers of Alzheimer’s disease and their immune cell infiltration correlation

Kun Zhao,
Yinyan Wu,
Dongliang Zhao
et al.

Abstract: BackgroundAlzheimer’s disease (AD), a neurodegenerative disorder with progressive symptoms, seriously endangers human health worldwide. AD diagnosis and treatment are challenging, but molecular biomarkers show diagnostic potential. This study aimed to investigate AD biomarkers in the peripheral blood.MethodUtilizing three microarray datasets, we systematically analyzed the differences in expression and predictive value of mitophagy-related hub genes (MRHGs) in the peripheral blood mononuclear cells of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 102 publications
(118 reference statements)
0
3
0
Order By: Relevance
“… Zhang et al (2023a) used PPI network, random forest, and two machine learning algorithms to obtain hub mitochondrial-related differentially expressed genes (MitoDEGs) closely related to AD. Zhao et al (2023) identified six mitophagy-related hub genes (MRHGs) that be used as valuable diagnostic biomarkers for AD.…”
Section: Identification Of Candidate Biomarkers Associated With the B...mentioning
confidence: 99%
See 1 more Smart Citation
“… Zhang et al (2023a) used PPI network, random forest, and two machine learning algorithms to obtain hub mitochondrial-related differentially expressed genes (MitoDEGs) closely related to AD. Zhao et al (2023) identified six mitophagy-related hub genes (MRHGs) that be used as valuable diagnostic biomarkers for AD.…”
Section: Identification Of Candidate Biomarkers Associated With the B...mentioning
confidence: 99%
“…Sirkis et al (2023) explores the association of early-onset Alzheimer's disease (EOAD) with specific peripheral immune signatures, and single-cell RNA sequencing identified significant expansion of a CD4 T cell termed interferon (IFN) signalingassociated gene (ISAG) hi T cells. Lin et al (2023) has explored the association between high-fat diet and AD and T2D. Analysis of singlecell RNA-seq (scRNA-seq) data indicated C4b is astrocyte-specific.…”
Section: Single-cell Sequencing and Spatial Transcriptomementioning
confidence: 99%
“…Microarray analysis and gene sequencing have been widely applied to explore the potential biomarkers or therapeutic targets of AD. After using 3 microarray datasets to screen mitogen-related hub genes in peripheral blood mononuclear cells of AD patients, 53 differentially expressed genes (DEGs) of AD are identified, which may serve as possible biomarkers for the diagnosis of AD [ 11 ]. LncRNA RP11-59 J16.2 may be a molecular target for AD, according to microarray analysis of blood from AD patients and healthy controls to determine LncRNA and mRNA expression profiles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%